O NOME QUE EU (NÃO) SOU: retificação de nome e sexo de pessoas transexuais e travestis no registro civil. - SOUSA, Tuanny Soeiro (2015)
This paper analyzes the answers given by the Judiciary to the cases of name rectification and legal gender in the civil registry of transsexual people and travestis. The necessity of this study arises from the fact that the Brazilian legal system does not provide exceptions to situations where gender contrast with the information on identification documents, which is an experience that these individuals go through. On the opposite of what they are required to be, the transsexual people and the travestis live gender differently from the rules created in the context of heterosexism, which demand coherence and continuity among sex, gender and sexuality. The main objective consists of questioning the discourses produced in the juridical field by the magistrates responsible for the trial and consequently the ruling of these cases. To achieve that, this paper studies, through the analysis of documents and bibliographic reviews, some rulings that deal with the modification of data in the civil registry of transgenders. In the first chapter, the concepts of “discourse”, “power”, and “truth” are analyzed from the French Discourse Analysis point of view of Michel Foucault, presenting the ideas of Michel Miaille and Clemerson Merlin Clève with the purpose of understanding the discourse aspects of Law. In the second chapter, statements such as sex, gender, sexuality and transsexuality, are examined mainly through Judith Butler. In the third chapter, some rules that deal with the right to have a name, as well as the possibilities and the ways of modifying information from the civil registry are investigated. In addition, some Brazilian rulings related to this subject are analyzed through bibliographic review. In the end, the rulings given in the state of Maranhão are examined. The results of the research demonstrate that the state of Maranhão, contrasting with the national reality, has been partially given positive answers to the cases involving transsexual individuals, mainly through the recognition of the importance of the rectification to the travesties and the transsexual men and women who have not undergone the sex reassignment surgery.